1998
DOI: 10.1097/00000658-199806000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone: The Crucial Hormone Responsible for Depressing Myocardial Function in Males After Trauma-Hemorrhage

Abstract: ObjectiveTo determine whether testosterone depletion in males before trauma-hemorrhage has any salutary effects on cardiac performance after hemorrhage and resuscitation. Summary Background DataStudies indicate that castration of male mice before traumahemorrhage prevents the immunodepression seen after hemorrhage and resuscitation. However, the effect of precastration on cardiac performance under such conditions remains unknown. MethodsMale rats were castrated or sham-castrated 14 days before the experiment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 36 publications
(6 reference statements)
4
54
0
2
Order By: Relevance
“…These results are similar to our previous findings (19,34,39,41). E 2 treatment (0.5 mg/300 g body wt, 1 wk Fig.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to our previous findings (19,34,39,41). E 2 treatment (0.5 mg/300 g body wt, 1 wk Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Using rodent models of acute illness, these studies have reported improved cardiovascular, hepatic, renal, pulmonary, and immune function as well as decreased mortality in situations where more circulating estrogen is present (11,14,15,19,20,30,65). These improvements in organ functions and in mortality were also observed when testosterone effect was reduced by either orchiectomy or flutamide, a potent androgen blocker (2,30,35,37,38,62,65). Further translational studies blending animal and human models are of interest to explore the clinical significance of these findings.…”
Section: Ajp-endocrinol Metabmentioning
confidence: 96%
“…Additional studies are of interest because reports in animal models suggest that the hypogonadotropic hypogonadism and accompanying increased estrogen production may be adaptive (2,11,14,15,19,20,30,35,37,38,62,65). Using rodent models of acute illness, these studies have reported improved cardiovascular, hepatic, renal, pulmonary, and immune function as well as decreased mortality in situations where more circulating estrogen is present (11,14,15,19,20,30,65).…”
Section: Ajp-endocrinol Metabmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, trauma surgeons began to investigate the special care of single injuries [8,89] but especially interaction of these injuries and their systemic effects on the circulatory and immune system [24,68,69]. Therefore, interdisciplinary shock research groups have been created at several trauma centers, fostering interdisciplinary, joint efforts by trauma surgeons and basis scientists [25,57].…”
Section: Effects Of Clinical and Experimental Research On In-hospitalmentioning
confidence: 99%